Alsinol, an arylamino alcohol derivative active against Plasmodium, Babesia, Trypanosoma, and Leishmania: past and new outcomes - Arias, Maria H. (2020)
Malaria, babesiosis, trypanosomosis, and leishmaniasis are some of the most life-threatening parasites, but the range of drugs to treat them is limited. An effective, safe, and low-cost drug with a large activity spectrum is urgently needed. For this purpose, an aryl amino alcohol derivative called Alsinol was resynthesized, screened in silico, and tested against Plasmodium, Babesia, Trypanosoma, and Leishmania. In silico Alsinol follows the Lipinski and Ghose rules. In vitro it had schizontocidal activity against Plasmodium falciparum and was able to inhibit gametocytogenesis; it was particularly active against late gametocytes. In malaria-infected mice, it showed a dose-dependent activity similar to chloroquine. It demonstrated a similar level of activity to reference compounds against Babesia divergens, and against promastigotes, and amastigotes stages of Leishmania in vitro. It inhibited the in vitro growth of two African animal strains of Trypanosoma but was ineffective in vivo in our experimental conditions. It showed moderate toxicity in J774A1 and Vero cell models. The study demonstrated that Alsinol has a large spectrum of activity and is potentially affordable to produce. Nevertheless, challenges remain in the process of scaling up synthesis, creating a suitable clinical formulation, and determining the safety margin in preclinical models.